The impact of perceptions of tax compliance quality: an exploratory study in Malaysia - Chong, K-Rine; Ravindran, Ramasamy; Abdul Rashid, Md. Zabid; Amat Sapuan, Dewi (Perpustakaan Sultan Abdul Samad, Universiti Putra Malaysia, 2015)
As the economic factors are insufficient to explain tax compliance behaviour, tax literature evolves to socio-psychological factors. This study extends the “slippery slope framework” to further investigate how perceptions impact on voluntary compliance and enforced compliance. Quota sampling was employed with 340 usable responses from the self-employed group, employed group and student group in Malaysia. SEM Amos was conducted for hypotheses testing in addition to model fit assessment. The findings indicate that perceptions of power of authorities and trust in government enhance both dimensions of compliance quality, whereas trust in tax authorities merely increases enforced compliance. Besides that, conditional cooperation reduces voluntary compliance, while tax awareness enhances voluntary compliance. This paper tested the framework in an Asian context and more importantly, it contributes to the literature by exploring the impact of different dimensions of trust and morale on compliance. Furthermore, findings and inferences would help the policy makers to adapt appropriate strategies to optimize tax revenue.